Biogas Production from Vegetable Waste by Using Dog and Cattle Manure. (November 2015) - Phetyim, Natacha; Wanthong, Tawanna; Kannika, Phijittra; Supngam, Anuwat
Abstract: This research investigates the effect of ratios between dog and cattle manures on anaerobic digestion in batch digesters under mesophilic conditions. The batch test was conducted for 28 days. Mixed Chinese cabbage and cabbage as the major wastes have been filled up in 200-liter digester. The vegetable wastes loading per day were studied under the specific increasing loaded weight as 0.5 kg and 1.0 kg each week. The additional waste load of 1.0 kg showed the optimum condition with the high biogas yield. The biogas accumulated from dog manure 10 wt% and 20 wt% were calculated using total amount of biogas produced per day; the results were 0.602 m 3 and 0.711 m 3, respectively. The methane content increased used higher percentage of dog manure.